METODE CIRCUIT TRAINING MENINGKATKAN DAYA TAHAN OTOT TUNGKAI PADA PEMAIN EKSTRAKURIKULER FUTSAL SMP ROUDLOTUL ULUM - Ahyer, Nor Moh; Himawan, Agus; Handayani, Heni Yuli; Faisal, Bagus Imam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the extent to which the circuit training method can increase the leg muscle endurance of futsal players at SMP Roudlotul Ulum. This study uses an experimental method on one group without a comparison using a pretest-posttest design where the pretest is the initial measurement and the posttest is the final measurement with the treatment given, namely the Circuit training method. The population of this study were students of SMP Roudlotul Ulum. The sampling technique used was Purposive Sampling with the criteria of students who took part in futsal extracurricular activities so that a sample of 7 was obtained. Circuit training in this study with a frequency of 3 times a week for 24 face-to-face meetings (4 weeks) consisting of 12 posts per training session. The instrument for measuring leg muscle endurance in this study used the Wall Squat Test. Data analysis in this study used SPSS which included descriptive tests, normality tests, and Wilcoxon tests. The results of the Wilcoxon test showed Sig 0.018 <0.05. The conclusion of this study is that there is a significant influence of the circuit training method on leg muscle endurance in extracurricular futsal players at SMP Roudlotul Ulum. In addition, the mean results also show that there is a significant influence of the circuit training method on leg muscle endurance in extracurricular futsal players at SMP Roudlotul Ulum, which has increased significantly.